ANALISIS PENGGUNAAN MEDIA PEMBELAJARAN DALAM PEMBELAJARAN MODEL TEMATIK CONNECTED DI SEKOLAH DASAR: PENYELIDIKAN KAITANNYA DENGAN MINAT BELAJAR SISWA DI SDN 36 CAKRANEGARA - Saniswari, Ida Ayu Nyoman; Ermiana, Ida; Kareninda, Ida Ayu Putu; Badrawati, Ida Sri; Nurdiana, Ilda (Jurusan Ilmu Pendidikan FKIP Universitas Mataram, 2025)
This study aims to analyze the use of learning media in the thematic connected learning model and its relationship with students’ learning interest at SDN 36 Cakranegara. The learning media used include concrete objects, interactive PowerPoint presentations, and interactive games. This qualitative research employed observations, interviews, and documentation to collect data. The results show that the use of learning media significantly increases students’ learning interest, reflected in enhanced participation, enthusiasm, and active involvement during the learning process. The media help students better understand the material and reduce boredom commonly experienced with traditional lecture methods. Furthermore, the application of the connected learning model integrated with learning media supports comprehensive understanding of concepts and skills. This study concludes that utilizing learning media is an effective strategy to improve students’ learning interest and the quality of education in elementary schools.